Levothyroxine sodium loaded dissolving microneedle arrays for transdermal delivery - Riyam Faisal Ghazi; Mohammmed Hussain Al-Mayahy (International Association of Physical Chemists (IAPC), 2022)
Levothyroxine (LT-4) sodium has shown variable bioavailability following oral administration. This can be assigned to the significant influence of gastrointestinal conditions, food and drugs administered concomitantly on the rate and extent of absorption from the gastrointestinal tract. Thus, the aim of this research study was to establish an efficient transdermal delivery system of LT-4 sodium via the application of hyaluronic acid dissolving microneedles. Microneedles-based drug delivery system consists of sharp-tip needles that puncture the top layers of the skin in a minimally invasive manner to create physical channels through which therapeutic molecules can easily diffuse into/across the skin. Hyaluronic acid polymer at different ratios (5-60 %) was used to prepare microneedle arrays (100 needles per array) using a micromoulding technique. Characterisation tests were carried out to select the optimum formulation. F11 formula containing 50% w/v hyaluronic acid and 1% v/v Tween 80 formula showed an appropriate needle shape with dimensions of 432 ± 6.4 μm in height and a tip diameter of 9.8 ± 1.3 μm. The microneedle arrays demonstrated a suitable mechanical strength after applying a force of 32 N per array and an excellent insertion ability both in Parafilm M® and human skin. The in vivo dissolution of microneedles was started rapidly within 5 minutes following the insertion in the skin and completed at 1 hour. Ex vivo permeation study using human skin has shown a significant improvement in LT-4 sodium delivery across the skin compared to control preparations (drug solution and microneedle free film). The microneedle array F11 has significantly (P ≤ 0.05) increased LT-4 sodium permeation through the skin (cumulative permeated amount of 32 ± 2 µg/cm²) in comparison to the control solution (cumulative permeated amount of 0.7 ± 0.07 µg/cm²) and the microneedle free film (cumulative permeated amount of 0.1 ± 0.02 µg/cm²) over 7 hours. The findings from the irritation test revealed that mild erythema was produced from the application of microneedle arrays which disappeared within 24 hours. Accordingly, dissolving hyaluronic acid microneedles could be a feasible and effective approach to delivering LT-4 sodium transdermally without causing significant skin damage.